Direct Identification of an HPV-16 Tumor Antigen from Cervical Cancer Biopsy Specimens - Keskin, Derin B.; Reinhold, Bruce; Lee, Sun Young; Zhang, Guanglan; Lank, Simon; O'Connor, David; Berkowitz, Ross S.; Brusic, Vladimir; Kim, Seung Jo; Reinherz, Ellis L. (Frontiers in Immunology, 2011)
Persistent infection with high-risk human papilloma viruses (HPV) is the worldwide cause of many cancers, including cervical, anal, vulval, vaginal, penile and oropharyngeal. Since T cells naturally eliminate the majority of chronic HPV infections by recognizing epitopes displayed on virally altered epithelium, we exploited Poisson detection mass spectrometry (MS3) to identify those epitopes and inform future T cell-based vaccine design. Nine cervical cancer biopsies from HPV-16 positive HLA-A*02 patients were obtained, histopathology determined, and E7 oncogene PCR-amplified from tumor DNA and sequenced. Conservation of E7 oncogene coding segments was found in all tumors. MS3 analysis of HLA-A*02 immunoprecipitates detected E711-19 peptide (YMLDLQPET) in seven of the nine tumor biopsies. The remaining two samples were E711-19 negative and lacked the HLA-A*02 binding GILT thioreductase peptide despite possessing binding-competent HLA-A*02 alleles. Thus, the conserved E711-19 peptide is a dominant HLA-A*02 binding tumor antigen in HPV-16 transformed cervical squamous and adenocarcinomas. Findings that a minority of HLA-A*02:01 tumors lack expression of both E711-19 and a peptide from a thioreductase important in processing of cysteine-rich proteins like E7 underscore the value of physical detection, define a potential additional tumor escape mechanism and have implications for therapeutic cancer vaccine development.